2002
DOI: 10.1111/j.1582-4934.2002.tb00512.x
|View full text |Cite
|
Sign up to set email alerts
|

Biomedical applications of protein chips

Abstract: The development of microchips involving proteins has accelerated within the past few years. Although DNA chip technologies formed the precedent, many different strategies and technologies have been used because proteins are inherently a more complex type of molecule. This review covers the various biomedical applications of protein chips in diagnostics, drug screening and testing, disease monitoring, drug discovery (proteomics), and medical research. The proteomics and drug discovery section is further subdivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 94 publications
0
11
0
Order By: Relevance
“…Innovative antibody-based methods to improve protein measurements, such as stable isotope standards and capture by anti-peptide antibodies (SISCAPA), are already being applied in mass spectrometry platforms to quantify peptides in complex mixtures (21). Additionally the combination of microarray technology and proteomics reagents has led to the development of "proteome chips," which offer the potential for the multiplexed analysis of hundreds to thousands of proteins in parallel (22,23). These chips represent a promising application for large scale, cost-effective screening for numerous proteomics applications, including identifying protein-drug and protein-lipid interactions and post-translational modifications (24).…”
Section: Affinity Capture Reagents In Discovery and Translational Resmentioning
confidence: 99%
“…Innovative antibody-based methods to improve protein measurements, such as stable isotope standards and capture by anti-peptide antibodies (SISCAPA), are already being applied in mass spectrometry platforms to quantify peptides in complex mixtures (21). Additionally the combination of microarray technology and proteomics reagents has led to the development of "proteome chips," which offer the potential for the multiplexed analysis of hundreds to thousands of proteins in parallel (22,23). These chips represent a promising application for large scale, cost-effective screening for numerous proteomics applications, including identifying protein-drug and protein-lipid interactions and post-translational modifications (24).…”
Section: Affinity Capture Reagents In Discovery and Translational Resmentioning
confidence: 99%
“…For example, the studies described in Subheading 4.2.1. relating the expression ofNHEJ factors to radiosensitivity were potentially compromised by our incomplete knowledge of the genes/proteins involved in that pathway (314), such that limiting screening to known repair factors might not always give correlations with radiosensitivity. However, the advent of cDNA microarrays (315,316) and, more recently, protein chip technologies (317)(318)(319) has enabled the rapid screening of thousands of genes and proteins without the prerequisite for knowledge of their activity. The expression profile of genes believed to be involved in radiosensitivity has recently been characterized by microarrays in cervical cancer cell lines (320) and inhead and neck cancer (321).…”
Section: Discussionmentioning
confidence: 99%
“…The design of diagnostic protein chips has focused on clinical applications (23,24 ). Ekins and Chu (25 ) suggested that quantitative immunoassays could be developed that use microspots of antibodies on nonporous solid supports, thereby enabling multianalyte assays, but it was only recently that such testing biochips have become a reality (26 -29 ).…”
Section: Discussionmentioning
confidence: 99%